Long-term in vitro degradation behaviour of Fe and Fe/Mg2Si composites for biodegradable implant applications. Issue 18 (6th March 2018) - Sikora-Jasinska, M.; Chevallier, P.; Turgeon, S.; Paternoster, C.; Mostaed, E.; Vedani, M.; Mantovani, D.
Abstract : This fundamental study provides a basis for the processes of protective film formation on degradable Fe-based biomaterials. Abstract : The major drawback of Fe-based materials for biodegradable implant applications is their slow degradation rate. Addition of second phase particles into the Fe matrix can increase the degradation rate at the beginning of the corrosion process. However, so far, there is neither quantitative data on in vitro degradation nor direct experimental evidence for long-term dissolution of Fe-based biodegradable composites. Here, a series of immersion tests at different exposure intervals (20, 50 and 100 days) to modified Hanks' solution were performed to study the degradation behavior of Fe and Fe/Mg2 Si composites prepared by different powder metallurgy techniques. The results revealed the role of Mg2 Si in the composition and stability of the protective films formed during the static corrosion experiments. Fe/Mg2 Si composites showed higher degradation rates than those of pure Fe at all stages of immersion. Degradation rates at distinct exposure intervals strongly depended on the composition and stability of formed oxide, hydroxide, carbonate and phosphate protective films on the degraded surfaces. The release of Fe ions into the solution at later stages of the experiment was limited due to the barrier effect of the insoluble deposit. This fundamental study provided a basis for the processes of protective film formation in modified Hanks' solution, which enables a detailed identification of its characteristic features.